2005
DOI: 10.1038/sj.ejcn.1602272
|View full text |Cite
|
Sign up to set email alerts
|

Obesity prevention in low socioeconomic status urban African-American adolescents: study design and preliminary findings of the HEALTH-KIDS Study

Abstract: Objectives: Obesity prevention among children and adolescents is a public health priority; however, limited school-based intervention trials targeting obesity have been conducted. This article provides an overview of the study design and baseline preliminary findings of our ongoing school-based intervention study. Design: Randomized intervention trial to test a school-based, environmental obesity prevention program in urban low socioeconomic status (SES) African-American adolescents. The intervention program w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 38 publications
(64 reference statements)
0
46
0
Order By: Relevance
“…Currently we are in the follow-up and evaluation phase of the study. More details about the study design are provided elsewhere 15 . Fig.…”
Section: Overview Of Study Designmentioning
confidence: 99%
“…Currently we are in the follow-up and evaluation phase of the study. More details about the study design are provided elsewhere 15 . Fig.…”
Section: Overview Of Study Designmentioning
confidence: 99%
“…[24][25][26] While the literature on intervention is limited and focuses on early adolescents, studies have consistently shown that school-based interventions are desperately needed and can be effective. [27][28][29][30][31] For example, Planet Health, an interdisciplinary school intervention for early adolescents in Massachusetts, reduced television viewing hours overall in boys and girls, increased fruit and vegetable consumption and smaller increment in energy intake in girls, and decreased obesity among girls. 32 Alternatively, a randomized trial of school-based environmental and policy changes among early adolescents was successful in increasing physical activity and reduced BMI among boys.…”
Section: Discussionmentioning
confidence: 99%
“…It is consistent with a lot of obesity intervention measures. Neumaek-Sztainer et al [15] and Wang Y et al [16] increase physical exercise and teach the benefits of physical exercise to improve students' activity level, so as to achieve the goal of weight loss.…”
Section: Relationship Between the Impulsivity Eating Behavior And Acmentioning
confidence: 99%
“…It includes 30 entries, which is divided into six factors: attention factor, exercising factor, self-control factor, cognitive complexity factor, stability factor and cognitive instability factor. According to the frequency of each entry, the record is graded from 1 to 4 ("hardly/never" = 1; "occasionally" = 2; "often" = 3; "almost always or always" = 4), in which the 11 entries (4,5,13,14,15,16,17,19,20,21,26) are reverse scoring. The higher the total score of questionnaire is, the higher the level of individual impulsivity is.…”
Section: Bis-11 Scalementioning
confidence: 99%